Multicultural education through halal bi halal activities in the merbau padangsari banyumanik semarang community - Zaenal Abidin; Marzuki; Hamilaturroyya; Maulia Indana Zulfa; Yusron Kamal (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This study aims to examine how Halal bi Halal activities become a means of multicultural education in the Merbau Padangsari community, Banyumanik, Semarang. Halal bi Halal activities, which are an annual tradition after Eid al-Fitr, are seen not only as a means of friendship, but also as an effective medium in fostering values ​​of tolerance, mutual respect, and harmony among residents who have diverse cultural and religious backgrounds. This study uses a qualitative approach with a case study method. Data were collected through participatory observation, in-depth interviews with community leaders, and documentation of activities. The results of the study indicate that Halal bi Halal has a significant role in strengthening social harmony and expanding community understanding of the importance of multicultural values ​​in community life. The hypothesis that this activity is a means of inclusive social and cultural learning is acceptable. These findings strengthen the argument that local traditions have the potential as instruments of character education and multiculturalism at the community level.